Molecular cloning and phylogenetic analysis of the E gene of transmissible gastroenteritis virus (TGEV) isolated in China - D. L. Lan, J. P. Gu, R. Xing, C. L. Yuan, L. Cui, X. G. Hua; Z. B. Yang (African Journal of Pig Farming, 2020)
Porcine transmissible gastroenteritis caused by transmissible gastroenteritis virus (TGEV) induces acute, high-contact intestinal infectious diseases in pigs. TGEV encodes four structural proteins including spike (S), membrane (M), envelope (E) and nucleoprotein (N), of these, the genes of S, M and N respectively had been deeply elucidated. However, the real function of E protein was still unclear and sequence comparison of the E gene of different TGEV isolates had not been reported so far. In this study, E gene of TGEV strain isolated in China was molecularly cloned and sequenced. Phylogenetic analysis confirmed this gene was relatively conserved. All the China TGEV strains were brached in one clade together with the American strains, but showed relatively alien to the European strains